The Methodological Unboundedness of Limited Discovery Processes - Cassel, John Benjamin (FormAkademisk, 2014)
Though designers must understand systems, designers work differently than scientists in studying systems. Design engagements do not discover whole systems, but take calculated risks between discovery and intervention. For this reason, design practices must cope with open systems, and unpacking the tacit guidelines behind these practices is instructive to systems methodology. This paper shows that design practice yields a methodology which applies across forms of design. Design practice teaches us to generate ideas and gather data longer, but stop when the return on design has diminished past its cost. Fortunately, we can reason about the unknown by understanding the character of the unbounded. We suppose that there might as well be an infinite number of factors, but we can reason about their concentration without knowing all of them. We demonstrate this concept on stakeholder systems, showing how design discovery informs systems methodology. Using this result, we can apply the methods of parametric design when the parameters are not yet known by establishing the concentration of every kind of factor, entailing a discovery rate of diminishing returns over discovery activities, allowing the analysis of discovery-based trade-offs. Here, we extend a framework for providing metrics to parametric design, allowing it to express the importance of discovery.